2007
DOI: 10.1111/j.1540-8175.2007.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Diastolic Function of Ankylosing Spondylitis Patients by Using Conventional Pulsed Wave Doppler, Myocardial Performance Index and Tissue Doppler Imaging

Abstract: When sensitive echocardiographic Doppler techniques such as MPI, TDI-derived MPI, and PW-TDI are utilized, DD can be detected in a significant proportion of patients with AS without cardiovascular (CV) disease which may contribute CV mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
(96 reference statements)
4
26
0
Order By: Relevance
“…In a study of 49 patients with AS (mean age 38 AE 11 years), Okan et al (15) detected a significant proportion of patients with DD without cardiovascular disease. An é/á ratio < 1.0 was observed in 45% of the patients.…”
Section: Dd In Relation To Demographics Disease Activity and Cardiomentioning
confidence: 98%
See 1 more Smart Citation
“…In a study of 49 patients with AS (mean age 38 AE 11 years), Okan et al (15) detected a significant proportion of patients with DD without cardiovascular disease. An é/á ratio < 1.0 was observed in 45% of the patients.…”
Section: Dd In Relation To Demographics Disease Activity and Cardiomentioning
confidence: 98%
“…Abnormalities in left ventricular (LV) diastolic dysfunction (DD) have also been observed in patients with AS (12)(13)(14)(15). However, these previous studies have reported varying incidences of DD, which may be related to the use of different imaging modalities.…”
mentioning
confidence: 93%
“…The severity of cardiac involvement varies greatly ranging from asymptomatic to severe considerable problems such as severe heart failure, and arrhythmias (3). Some studies revealed an increased prevalence of cardiovascular (CV) mortality in AS (4)(5)(6)(7)(8).…”
Section: Ankylosing Spondylitis (As) Is a Chronic Inflammatory Diseasmentioning
confidence: 99%
“…Figure 4 shows the tissue Doppler recording at the level of the lateral tricuspid annulus. The reduced early (E ) diastolic myocardial relaxation velocity combined with the reduced ratio of E to the late (A ) velocities (<1) 6,7 indicate the presence of right ventricular diastolic dysfunction in our patient. Another potential contributing factor could be the development of diastolic tricuspid regurgitation causing reduction of end diastolic right ventricular pressure and reestablishment of the gradient between the pulmonary artery and the right ventricle.…”
Section: Discussionmentioning
confidence: 88%